An Analysis of Student Learning Motivation Gender Perspective At SMA N 2 Lintau Buo, West Sumatra - Suryani, Irda; Pranata, Rudi; Desmita, Desmita; Erizal, Zulfa (AGENDA: Jurnal Analisis Gender dan Agama, 2022)
This research begins with a review of several findings which show that students' learning motivation is in the medium or even low category. It was revealed by the results of research, Rahmi (2012) that student motivation was 15.3% in the high category, 69.2% in the medium category, 15.5% in the low category. The researcher's initial assumption showed that female students were more motivated in learning compared to male students. From the research results, some literature states that some male students have low learning motivation due to attention, lack of desire to learn. It can be seen from the low motivation of students to do homework and do exercises at school, while female students tend to be diligent and systematic in dividing time to study and carry out schoolwork.